IMPACT OF SEED WEIGHT ON GERMINATION PARAMETERS OF CALOPHYLLUM INOPHYLLUM L.: A POTENTIAL BIODIESEL TREE SPECIES OF COASTAL REGION - R. AJEESH; C. M. JIJEESH; K. VIDYASAGARAN; KUMAR, VIKAS (The Bioscan, 2014)
We studied the variation in seed physical and biochemical attributes in different weight classes and to find out the influence of seed weight on germination parameters of Calophyllum inophyllum L. The fruits were obtained from the coastal areas of Thiruvananthapuram, Kerala during May-June 2012. Prominent size variation was observed among the fruits of the same lot and the seeds were extracted after drying. The seeds were graded based on their weight in to classes 2-5, 5-8 and 8-11 g. Number of fruits per kg of 8-11, 5-8 and 2-5 g weight classes was 116.0±17.7, 166.7±18.7 and 262.0±65.6 and thousand seed weight was 8.55±.24, 6.60±0.30 and 5.07±1.53 kg, respectively. With regards to individual seed characters, seeds belonging to 8-11 g class recorded a higher weight (8.62±0.59 g), length (3.24±0.18 cm), breadth (2.99±1.17 cm) and volume (0.12±0.01 cm3) compared to other classes. The biochemical constituents also decreased with decreasing weight class and the oil content of large seeds were 63 %. However, the germination percentage were the highest in medium sized seeds (68.00±3.00) followed by large seeds (68.00±2.00). Hence, the medium sized seed can be advocated for planting stock production in the nursery and followed by large seeds and small seeds.